Concurrent infection of Cryptosporidium and Giardia in synanthropic rodents: First report from Punjab, India - Brar, Sukhmanpreet Kaur; Singla, Neena; Singla, Lachhman Das (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present morphometric coproscopic study was aimed to investigate the protozoan infections in synanthropic rodents of urban areas from Punjab. Faecal samples of total 65 rodents of two species i.e. the house rat, Rattus rattus (n=40) and the lesser bandicoot rat, Bandicota bengalensis (n=25) collected from residences/shops, poultry farms and fish market at Ludhiana (Punjab), India were examined by formaldehyde–ether sedimentation and modified kinyoun acid fast stain for the presence of protozoan parasites. Cryptosporidium oocysts were detected in 32.30% rats comprising 36% B. bengalensis and 30% R. rattus. Morphometric examination of the acid-fast stained faecal smear revealed ovoid oocysts (average size of 7.70-9.8 x 5.5-7.0 μm) of Cryptosporidium whose morphology resembled that of C. muris. Precysts/cysts of Giardia sp. were also identified in 4.61% of the stained faecal smears. This is the first report of concurrent C. muris and Giardia sp. infections in synanthropic rodents of urban domestic and peridomestic area of Punjab, India.